2020
DOI: 10.3389/fmicb.2020.01461
|View full text |Cite
|
Sign up to set email alerts
|

Selenomethionine Suppressed TLR4/NF-κB Pathway by Activating Selenoprotein S to Alleviate ESBL Escherichia coli-Induced Inflammation in Bovine Mammary Epithelial Cells and Macrophages

Abstract: Inflammation is the hallmark of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli-induced bovine mastitis. Organic selenium can activate pivotal proteins in immune responses and regulate the immune system. The present study aimed to investigate whether selenomethionine (SeMet) attenuates ESBL E. coli-induced inflammation in bovine mammary epithelial cells (bMECs) and macrophages. Cells were treated with 0, 5/10, 10/20, 20/40, or 40/60 µM SeMet for 12 h and/or inoculated with ESBL-E. coli [multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…In addition, it reduces LPSinduced inflammation by inhibiting the NF-kB pathway, by enhancing the expression of selenoproteins, caspase 8, IkB-α, necroptosis markers (FADD, RIP1, RIP3, MLKL, and TNF-α), pro-inflammatory factors (NF-kB, PTGE, COX-2, iNOS, IL-1β, and IL-6), HSP60, HSP 70, and HSP 90. In addition, SLM modulates LPS-induced inhibition of the PI3K/AKT pathway and pro-inflammatory TLR4/NF-kb signaling pathway [104][105][106][107][108].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it reduces LPSinduced inflammation by inhibiting the NF-kB pathway, by enhancing the expression of selenoproteins, caspase 8, IkB-α, necroptosis markers (FADD, RIP1, RIP3, MLKL, and TNF-α), pro-inflammatory factors (NF-kB, PTGE, COX-2, iNOS, IL-1β, and IL-6), HSP60, HSP 70, and HSP 90. In addition, SLM modulates LPS-induced inhibition of the PI3K/AKT pathway and pro-inflammatory TLR4/NF-kb signaling pathway [104][105][106][107][108].…”
Section: Discussionmentioning
confidence: 99%
“…SLM modulation of the pro-inflammatory TLR4/NF-κB signaling pathway and macrophage activity was described in the study of inflammation of the mammary gland of cattle (mastitis) induced by E. coli. SLM attenuated inflammation caused by E. coli by modulating the transmission pathway signaling Toll-like receptor 4 (TLR4)/NF-κB and stimulated macrophages, enhancing their migration and activity [108].…”
Section: Role Of Selenomethionine In the Immune System And In Protect...mentioning
confidence: 99%
“…It has been reported that TGF-β1 participated in macrophages-mediated immune dysfunction during the progression of CKD ( 15 , 141 , 142 ). TGF-β1 largely increases macrophages infiltration and accumulation in the injured kidney via stimulating the release of a potent cytokine for macrophages recruitment monocyte chemoattractant protein-1 (MCP-1) from various types of renal cells ( 143 145 ). TGF-β1 also regulates macrophage polarization and immunomodulatory cytokines secretion.…”
Section: Tgf-β1 In Adaptive Immunity Of Ckdmentioning
confidence: 99%
“…The interactions between pathogen-associated molecular patterns (PAMPs), defined as highly conserved molecular structure in pathogenic microorganism, and pattern recognition receptors (PRRs) play an important role in the prevention and treatment of sepsis, including the recognition of infectious pathogens, the initiation of host inflammatory response and the activation of host immune defense [13][14][15]. Toll-like receptor (TLR) 4 activator, a typical PAMP with powerful biological functions, can regulate host inflammation, recruit granulocytes and macrophages to the infected sites and effectively promote pathogen clearance [16]. Furthermore, the insufficient activation of TLR4 signaling pathway in the host can promote the occurrence of infection and aggravate the progress of infection [1,17,18].…”
Section: Introductionmentioning
confidence: 99%